Commentary: Physical time within human time - Paganini, Elisa (Frontiers in Psychology, 2023)
A debate - involving philosophers, theoretical physicists, psychologists, and neuroscientists - focuses on whether the experience of the passage of time is a veridical or an illusory representation of the physical reality of the Universe. It is suggested here that a better understanding of illusions and hallucinations allows for a deeper examination of the role of time experience.